Intrahepatic distant recurrence after radiofrequency ablation of hepatocellular carcinoma: relationship with portal hypertension - Kim, Ran; Jeong, Woo Kyoung; Kang, Tae Wook; Song, Kyoung Doo; Lee, Min Woo; Ahn, Soo Hyun; Rhim, Hyunchul (Acta Radiologica, 2019)
Background: Portal hypertension might be used as a predictor for recurrence of hepatocellular carcinoma (HCC). The aim of this study was to determine whether the degree of portal hypertension assessed by computed tomography (CT) findings predicts intrahepatic distant recurrence (IDR) in patients with HCC after radiofrequency ablation (RFA). Material and Methods: This retrospective study was approved by the institutional review board. A total of 78 patients who received transient elastography before RFA were included. Two radiologists evaluated the size, number of index HCC, and gastroesophageal varices at risk of recurrence (GEV-R) by investigating variceal grades on CT. Liver stiffness measurements and laboratory fibrosis indices were also investigated. Recurrence-free survival rate was assessed using Kaplan–Meier curves, and each variable was evaluated using a Cox hazards model. A validation study was also performed with other patients who underwent RFA in the same institution (n = 89). Results: Cumulative recurrence-free survival rates were 79%, 51%, and 38% at 1, 2, and 3 years, respectively. GEV-R was defined as enlarged esophageal varix (≥2 mm diameter on CT) or gastric varix (≥10 mm diameter on CT). Multivariate analysis including CT features showed that GEV-R is a significant independent predictor of IDR (hazard ratio (HR) = 3.91; p = 0.002) as well as tumor multiplicity (HR = 2.79; p = 0.030). On validation study, tumor multiplicity (HR = 2.86; p = 0.006) was statistically significant, and GEV-R also showed increased tendency of recurrence (HR = 1.68; p = 0.083). Conclusion: CT-driven portal hypertension signs, such as the severity of varices could be a noninvasive predictor of IDR of HCC after RFA.
Keywords: esophageal varix; Hepatocellular carcinoma; Portal hypertension; Radio-frequency Ablation; recurrence; Adult; Aged; Carcinoma, Hepatocellular; Female; Humans; Hypertension, Portal; Liver; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Radiofrequency Ablation; Retrospective Studies; esophageal varix; Hepatocellular carcinoma; portal hypertension; radiofrequency ablation; recurrence